Sistem Informasi Pelayanan Tamu Berbasis Web Pada Badan Kepegawaian dan Pengembangan Sumber Daya Manusia Daerah Kota Jambi - Pebrianto, Feri; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2021)
Jambi City Regional Personnel and Human Resources Development Agency is a government implementer who has the task of assisting the mayor in matters of staffing education and training where at this time the system running at the Jambi City Regional Personnel and Human Resources Development Agency still uses a manual system and is less effective as in the recording process of guest services is still not structured and well recorded There is no report format to superiors as a basis for monitoring and evaluating the guest service system, therefore the authors study the management system of customer data guest services that are currently running at the Jambi City Regional Personnel and Human Resources Development Agency as well as making problem-solving solutions contained in the Jambi City Regional Personnel and Human Resources Development Agency such as designing guest service systems and making reports. In designing this program as a researcher use research method waterfall thar research starting from the analysis of the design using a tool, namely UML which is limited to only prototypes. Results and production of guest service information systems, there are, help officers in managing guestbook data and making reports easier. We Hope in guest system service Jambi City Regional Personnel and Human Resources Development Agency through relevant officials can develop this information system by adding features about guest satisfaction assessment guest service system.